2015
DOI: 10.1186/s12967-015-0640-8
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and allogeneic transplantation

Abstract: The latest high-throughput sequencing technologies show that there are more than 1000 types of microbiota in the human gut. These microbes are not only important to maintain human health, but also closely related to the occurrence and development of various diseases. With the development of transplantation technologies, allogeneic transplantation has become an effective therapy for a variety of end-stage diseases. However, complications after transplantation still restrict its further development. Post-transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 110 publications
0
74
0
3
Order By: Relevance
“…Recent studies showed that gastrointestinal disorders after kidney transplantation were related to intestinal flora disorder [25]; the dosage of MPA might not be the major cause of the gastrointestinal disorder, although a slightly low level of hemoglobin was observed in the intensified group at 1 week after the operation; however, no significant differences were observed at 2 weeks, 1 month, 3 months, and 1 year between the intensified and standard groups. Severe anemia (hemoglobin < 60 g/L) occurred with almost identical frequencies in the 2 groups.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies showed that gastrointestinal disorders after kidney transplantation were related to intestinal flora disorder [25]; the dosage of MPA might not be the major cause of the gastrointestinal disorder, although a slightly low level of hemoglobin was observed in the intensified group at 1 week after the operation; however, no significant differences were observed at 2 weeks, 1 month, 3 months, and 1 year between the intensified and standard groups. Severe anemia (hemoglobin < 60 g/L) occurred with almost identical frequencies in the 2 groups.…”
Section: Discussionmentioning
confidence: 88%
“…The gut microbiota also influences immune responses by triggering differentiation of T H 17, regulatory and memory T cells and maturation in NKT cells. 135 Disturbances in the microbiome (dysbiosis) are linked to intestinal inflammation and increased prevalence of potentially harmful facultative anaerobic bacteria. 136 During HCT, patients experience dramatic alterations in the intestinal microbiota with marked decreases in overall bacterial diversity, increasing risk for aGvHD and BSI.…”
Section: Bloodstream Infection Preventionmentioning
confidence: 99%
“…At the level of mesenteric lymph node, one should discuss interaction with innate lymphoid cells via a RORγt nuclear receptor, which reduces local inflammation [29]. Preservation of these interactions allows the growth suppression of pathogenic microbiota, eliminate endogenous and exogenous pathogens, maintain structural integrity of intestinal epithelium.…”
Section: Positive Effects Of Directed Microbiota Correctionmentioning
confidence: 99%